Effects of Superliv Concentrate on the Growth, Immunocompetence Traits and Nutrient Retention of Commercial Broilers During Extreme Winter - Bhattacharyya, Amitav; Garg, Satish Kumar; Kumar, Vinod; Roy, Debashish; Ravikanth, K.; Maini , Shivi (International Journal of Poultry Science, 2012)
A study was conducted during the months of December-January involving sixty one week old broiler chickens, distributed into two experimental groups having three replicates of ten birds each. The birds of the first group were fed a basal diet (22.5% CP & 2830 K cal/kg ME) while the second group birds were fed a basal diet supplemented with a liver tonic, Superliv concentrate (Ayurvet Limited product) @ 50g/quintal. Body weight gain was significantly higher (P<0.05) in the Superliv concentrate group compared to the control group at 2nd week, 3rd week, 4th week and 5th week of age. FCR was significantly higher (P<0.05) in the Superliv concentrate group than control group during 1-4 wk period (1.9 vs 2.1) and 1-6 wk period (1.97 vs 2.17). Total immunoglobulins and mercaptoethanol resistant (IgG) antibody titer (log 2) values in response to sheep red blood cells (SRBC) was significantly higher (P<0.05) in the Superliv concentrate group compared to the control group. Further, mercaptoethanol sensitive (IgM) antibody titer (log 2) values in response to sheep red blood cells (SRBC) were apparently higher in the Superliv concentrate group compared to the control group. Cell mediated immune (CMI) response (foot web index) was significantly higher (P<0.05) in the Superliv concentrate group compared to the control group. There was no significant difference in the nutrient retention between the Superliv concentrate group and control group. Hence, it may be concluded that Superliv concentrate may be added to broiler diet during winter to elicit growth performance and immunocompetence traits of commercial broilers.